2018
DOI: 10.19082/7028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the self-management education program on the quality of life in people with chronic heart failure: a randomized controlled trial

Abstract: BackgroundChronic Heart Failure (CHF) is a syndrome that negatively affects a person’s Quality of Life (QOL). The efficient self-management education program increases the individual’s abilities and skills for following and participating in a long-term healthcare plan.ObjectiveThe aim of this study was to determine the effect of the self-management education program on QOL in people with CHF.MethodsThis randomized controlled trial study was conducted on 60 people with CHF and without sensory-cognitive problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…As shown by the SF-36 scores, FCIHE significantly improved the quality of life of our patients, which might be explained by the fact that patients in the intervention group gradually changed from passive nursing to active self-care after implementation of FCIHE, which accurately covered the patients’ daily drug use, diet, and exercise behavior and played an active role in regulating body status and controlling disease conditions[25-27]. In addition, Segan et al[28] reported that FCIHE established a progressive closed-loop nursing mode of self-care – guided care – self-care, which helped patients to optimize continuously their care measures during self-care and thus markedly improved their quality of life[28,29].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by the SF-36 scores, FCIHE significantly improved the quality of life of our patients, which might be explained by the fact that patients in the intervention group gradually changed from passive nursing to active self-care after implementation of FCIHE, which accurately covered the patients’ daily drug use, diet, and exercise behavior and played an active role in regulating body status and controlling disease conditions[25-27]. In addition, Segan et al[28] reported that FCIHE established a progressive closed-loop nursing mode of self-care – guided care – self-care, which helped patients to optimize continuously their care measures during self-care and thus markedly improved their quality of life[28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in diabetic patients and those with chronic heart failure have reported improved not only patient self-reported health, satisfaction, and quality of life but also better patient survival. [2][3][4][5] There have been few studies investigating self-care during hemodialysis and shared the responsibility of care. However, these limited studies have suggested that self-care during hemodialysis improved physical functioning, and greater knowledge of kidney disease and treatment improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Most ICHD patients take little if any, control of their hemodialysis treatment relying on the dialysis center health care professionals. Studies in diabetic patients and those with chronic heart failure have reported improved not only patient self‐reported health, satisfaction, and quality of life but also better patient survival 2‐5 . There have been few studies investigating self‐care during hemodialysis and shared the responsibility of care.…”
Section: Introductionmentioning
confidence: 99%
“…As only a minority of patients are suitable for transplantation, then for many patients HD is for life. 8 Indeed, studies in other chronic healthcare conditions, diabetes mellitus and congestive heart failure have reported that patients who take greater control of their own medical care 9-12 reported a reduction in emotional burden, 9 short-term improvement in glycaemic control, 10 over-all quality of life, 11 and shortterm changes in self-reported self-management skills predicted intermediate-term changes in improved mental quality of life and long-term changes in better physical quality of life. 1,2 Although the absolute rates of clinically diagnosed depression are much lower, 3 self-reported depression is associated with increased over-all mortality.…”
Section: Introductionmentioning
confidence: 99%
“…4 A number of psychological theories, including human becoming theory, Bandura's self-efficacy theory, and Orem's self-care model, [5][6][7] have suggested that patients who take greater care of their own medical care have less depression and are more motivated to perform and promote activities designed to maintain or improve health care. 8 Indeed, studies in other chronic healthcare conditions, diabetes mellitus and congestive heart failure have reported that patients who take greater control of their own medical care [9][10][11][12] reported a reduction in emotional burden, 9 short-term improvement in glycaemic control, 10 over-all quality of life, 11 and shortterm changes in self-reported self-management skills predicted intermediate-term changes in improved mental quality of life and long-term changes in better physical quality of life. 12 Self-help in HD is typically associated with home dialysis therapies, and as such the improvement in patient outcomes reported, 13 may be biased by patient selection.…”
Section: Introductionmentioning
confidence: 99%